Organizational Capacity in Implementing the “Kang Pisman” Program: A Case Study of Waste Management in Bandung City - Sumaryana, Asep; Komara, Syifa Rachmania; Pancasilawan, Ramadhan (Journal of Ecohumanism, 2025)
The issue of waste management in Indonesia, both at the national and local levels, has become an important topic worthy of research. Policies issued by the government to address and minimize waste problems, such as Presidential Regulation of the Republic of Indonesia Number 97 of 2017 on the National Policy and Strategy for Household Waste Management, as well as Bandung City Regional Regulation Number 17 of 2012 on Reducing the Use of Plastic Bags, demonstrate the government’s commitment to tackling this issue. The implementation of these policies is carried out through various programs, one of which is the "Kang Pisman" program (Reduce, Separate, and Utilize), which began with the Waste Collection Movement. This program, introduced in 2018, aims to raise public awareness about sustainable waste management. However, the success of its implementation is highly influenced by the capacity of local government organizations to plan, execute, and evaluate these policies. Organizational capacity, which includes aspects such as human resources, infrastructure, inter-agency coordination, and internal policy support, plays a significant role in the effectiveness of the Kang Pisman program. This study aims to analyze the correlation between the organizational capacity of the Bandung City local government and the success of the Kang Pisman program in addressing waste management issues. The results of this research are expected to provide insights into the importance of strengthening organizational capacity to support the sustainability of environmental policies.